1994
DOI: 10.1172/jci117385
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of band 3 lateral and rotational mobility in intact red cells.

Abstract: Measurements of integral membrane protein lateral mobility and rotational mobility have been separately used to investigate dynamic protein-protein and protein-lipid interactions that underlie plasma membrane structure and function. In model bilayer membranes, the mobilities of reconstituted proteins depend on the size of the diffusing molecule and the viscosity of the lipid bilayer. There are no direct tests, however, of the relationship between mechanisms that control protein lateral mobility and rotational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
64
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 65 publications
18
64
2
Order By: Relevance
“…If one or both of the D populations were to correspond to ankyrinand/or adducin-attached band 3, then this increase in band 3 mobility would be consistent with observations that linkages connecting the bilayer (primarily via band 3) to the spectrin skeleton are compromised in HS. [11][12][13][14] Similarly, the complete loss of the slow diffusing population of band 3 in HPP and the concomitant nearly complete loss of totally immobilized band 3 in the same cells would be consistent with published data demonstrating that the spectrin skeleton is extensively fragmented in HPP and that band 3-ankyrin affinity is influenced by spectrin tetramer formation 42 ; ie, in agreement with previous fluorescence recovery after photobleaching (FRAP) data from Golan and coworkers 43 showing that band 3 diffuses 6 times faster and has a smaller immobilized fraction in HPP cells than in any HS or normal sample examined (see Table 1). Moreover, the slower D values of band 3 in the SAO cells is consistent with the fact that band 3 forms linear aggregates in these cell types, 26,44 and the faster D in HE cells is not incompatible with the view that the spectrin network is weakened in this pathology.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If one or both of the D populations were to correspond to ankyrinand/or adducin-attached band 3, then this increase in band 3 mobility would be consistent with observations that linkages connecting the bilayer (primarily via band 3) to the spectrin skeleton are compromised in HS. [11][12][13][14] Similarly, the complete loss of the slow diffusing population of band 3 in HPP and the concomitant nearly complete loss of totally immobilized band 3 in the same cells would be consistent with published data demonstrating that the spectrin skeleton is extensively fragmented in HPP and that band 3-ankyrin affinity is influenced by spectrin tetramer formation 42 ; ie, in agreement with previous fluorescence recovery after photobleaching (FRAP) data from Golan and coworkers 43 showing that band 3 diffuses 6 times faster and has a smaller immobilized fraction in HPP cells than in any HS or normal sample examined (see Table 1). Moreover, the slower D values of band 3 in the SAO cells is consistent with the fact that band 3 forms linear aggregates in these cell types, 26,44 and the faster D in HE cells is not incompatible with the view that the spectrin network is weakened in this pathology.…”
Section: Discussionsupporting
confidence: 91%
“…Data of Golan et al 47 have further demonstrated that depletion of ankyrin releases the less mobile population from its rotational restriction and that the rotational and lateral diffusion of band 3 are independently regulated, the former by protein interactions at the cytoplasmic surface of the membrane, and the latter by the spectrin content of the cell. 43,48 Additional studies from the Golan laboratory 49 have also identified 2 populations of band 3 based on lateral diffusion measurements using FRAP. Finally, Kusumi and colleagues 7,50 introduced single-particle imaging methodologies to explore band 3 diffusion in erythrocyte ghosts, and they also identified 2 diffusing populations, albeit the diffusion coefficient of only the more mobile fraction was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DRMs may contain a portion of band 3 that has increased lateral mobility by virtue of being spectrin-and/or ankyrin-free. 30,31 Despite the controversy about the association of band 3 with erythrocyte DRMs, 3,12,19 we find that band 3 is indeed associated with DRMs and provides a major component of DRM rafts even under the most stringent conditions of erythrocyte DRM extraction reported in the literature. Previous studies have reported that cholesterol can be tightly associated with band 3, 32 and this may promote association with DRMs.…”
Section: Discussionmentioning
confidence: 50%
“…[1][2][3][4] Although the energetics of the membrane may be dominated by interactions of integral proteins within the bilayer, 5 the homogeneous spectrin skeleton modifies cell stability by modifying bilayer elasticity, by tethering or trapping membrane proteins so as to limit their lateral diffusability and ensure their quasi-random distribution, and by dampening the rate of protein rearrangement during cyclic cell deformation (as occurs during capillary passage).…”
Section: Introductionmentioning
confidence: 99%